فعالية الطريقة المغناطيسية التعليمية في تعليم النحو في مدرسة الثانوية مالانج - Muzayanah, Tika (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
Nahwu is one of the subjects given to students in order to support one's Arabic language skills. One of the current problems is the difficulty of students understanding the rules of the Arabic language, namely nahwu science, in addition to the fluctuating enthusiasm for student learning. This is caused by several factors, both internal and external factors. As a teacher, he has an important role in creating enthusiasm for learning among students in learning, especially learning Nahwu. One of the problems faced by teachers is the lack of mastery of different learning methods, and not adapting to the conditions of students This thesis discusses the Effectiveness of the Hypnoteaching Method in Nahwu Learning at MA At-Tarraqi, Malang. The aims of this study were: To find out the effectiveness of the hypnoteaching method in learning nahwu at MA At-Tarraqie Malang, East Java. This research is a type of experimental quantitative research. The research instruments used in this study were observation, tests (pre and posttest) and questionnaires. This research was conducted in class X (IPS) with 17 students and X (language) with 15 students. The results of this study, Because the data did not contribute normally, the researchers used the Mann Whitenay test. The results of the Mann Whitenay test show that the Asymp.Sig (2-tailed) value is 0.011 which is smaller than the probability value of 0.05 and it can be concluded that the use of the hypnoteaching method in learning nahwu is effective.